The in vitro Antiviral Mechanisms of Stronger Neo-Minophafen C, an Established Formulation of Compound Glycyrrhizin - Zhang, Chi; Li, Qi-Jie; Wang, Yi-Li; Chen, Jie; Lv, Chun-Yan; Liu, Wei-Wei; Chen, Li; He, Jia-Yue; Jiang, De-Yu; Xia, Xiu-Wen; Ding, Wei-Jun (Anti-Infective Agents, 2018)
Background: Glycyrrhiza glabra (liquorice) has been extensively used since ancient Egypt, Greek and Roman, and is an important herb in traditional Chinese medicine. Its major compound, Glycyrrhizin (GL) possesses multiple pharmacological activities, such as anti-virus waiting for exploration indepth. Objective: The aim of this research is determining the antiviral mechanisms of Stronger Neo-Minophafen C (SNMC), an established formulation of compound GL based on Interferon (IFN) system, an important cytokine family best known for its antiviral ability. Methods: Four cell lines, A549, Hela, SMMC-7721 and TC-1, were recruited. The relative cell viability (RCV) was measured with 3(4, 5 dimethylthiazol) 2, 5 diphenyltetrazolium bromide (MTT). The gene transcription of key elements on IFN system, such as IFN-β1, IRF3 and ISG15 were evaluated using realtime RT-PCR. The expressions of key enzymes on IFN system were measured by Western blot. The concentrations of IFN-γ and IRF1, representative members of type II interferon, were detected by ELISA. Results: SNMC reduces RCV with concurrent induction of antiviral genes majorly belong to type I IFN pathway, focusing on IRF3-IFN-β1- ISG15 axis. The expression of IFN-β1, IRF3 and ISG15 genes in A549 and Hela cells peak at 12 h post-SNMC incubation, in a time- and dosage- dependent manner. The expression of IFN-β1 protein reaches a peak at 24 h in A549 and SMMC-7721 cells, and peaks at 48 h in Hela and TC-1 cells. The expression of ISG15 reaches a peak at 24 h in A549, Hela and TC-1 cells, and at 48 h in SNMC-7721 cells. The expression of Mx reaches a peak at 24 h in A549 and Hela cells, and at 48 h in SMMC-7721 and TC-1 cells. However, SNMC could not induce the expression of type II IFN signal pathway. Conclusion: We demonstrated that SNMC can induce the expression of important anti-viral genes in type I interferon pathway and indicate the existence of a key pathway response for the anti-viral effects of SNMC.
Keywords: anti-viral activity